MENGAWUNG LANTUNG DALAM BUSANA PANGGUNG PENYANYI REMAJA PUTRI - Ardhisa Kus Prativya (Akademi Seni dan Desain Indonesia Surakarta, 2012)
Fashion planning in the task of this end of aiming at designing the fashion the stage of the singer of the daughter's adolescent with fashion style Lady Gaga. The material especially is bark lantung was combined with shimmer crush that reflected the blend of the past material with the technology material modern. The fashion promoted the motive kawung that was processed traditionally to bark lantung.The traditional process took the form of batik making in a manner wrote with the process pencantingan through to pelorotan â€œmalamâ€. Although having past material, bark lantung this could appear attracted with the combination shimmer crush that shone, was increased with a brightness of the goose hair, the application kawung-kawungan as well as the game of the texture in the fashion. This stage fashion consisted of three designs, two take the form of two pieces and one take the form of one piece. Used colours of nature, with the accent swarovski. As well as took the spirit Lady Gaga, apparently agile but stayed feminine. The design bervolume, slender on the waist as well as the game of geometric forms.